2017
DOI: 10.3233/nha-170026
|View full text |Cite
|
Sign up to set email alerts
|

Hydration health literacy in the elderly

Abstract: BACKGROUND:Inadequate hydration in the elderly is associated with increased morbidity and mortality. However, few studies have addressed the knowledge of elderly individuals regarding hydration in health and disease. Gaps in health literacy have been identified as a critical component in health maintenance, and promoting health literacy should improve outcomes related to hydration associated illnesses in the elderly.METHODS:We administered an anonymous survey to community-dwelling elderly (n = 170) to gauge th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 62 publications
1
43
0
4
Order By: Relevance
“…Alterations in the hydro-electrolytic balance may cause decreased muscle strength, gait instability, falls, fractures, respiratory infections, confusion, renal failure and increased medication toxicity and may increase the risk of death [53,54,55]. Despite several studies showing that the elderly are at an increased risk of dehydration-related health problems, there is little information on suitable liquid intake and hydration in the elderly [56]. There are no clear and objective clinical signs of early dehydration in the elderly, but plasma osmolarity can be considered the gold standard for a diagnosis of dehydration.…”
Section: Dehydration In the Elderlymentioning
confidence: 99%
“…Alterations in the hydro-electrolytic balance may cause decreased muscle strength, gait instability, falls, fractures, respiratory infections, confusion, renal failure and increased medication toxicity and may increase the risk of death [53,54,55]. Despite several studies showing that the elderly are at an increased risk of dehydration-related health problems, there is little information on suitable liquid intake and hydration in the elderly [56]. There are no clear and objective clinical signs of early dehydration in the elderly, but plasma osmolarity can be considered the gold standard for a diagnosis of dehydration.…”
Section: Dehydration In the Elderlymentioning
confidence: 99%
“…Drinking an adequate amount of fluid is essential to life across the lifespan (WHO, ). Yet, older adults are particularly at risk of dehydration due to decreased fluid intake and increased fluid loss (Picetti et al, ). In the UK, Regulation 14 of the Health and Social Care Act () acknowledges the importance of older people drinking sufficient fluid by emphasising the responsibility that care home providers have in ensuring that residents have adequate nutrition and hydration to sustain life and good health.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent cross-sectional study of elderly patients in the UK found that only 11% of patients met the minimum recommended fluid intake of 1.5 L/day and that 67% drank half the required fluid intake or less [43]. Given that water needs of individuals vary depending on differences in metabolism including environmental conditions, a one-size-fits-all approach to fluid intake may not be ideal particularly in the elderly [32,33]. Weightbased fluid intake has been recommended in this population but the effectiveness of this approach is yet to be demonstrated [44].…”
Section: Discussionmentioning
confidence: 99%